War women - Limón, Martin, 1948- (Limón, Martin, 1948- Sergeants Sueño & Bascom mystery, 2021)
"South Korea, 1970s: Sergeant First Class Cecil B. Harvey, a senior NCO in charge of 8th Army's classified documents, has long been a friend (willing or unwilling) to Sergeants George Sueño and Ernie Bascom. So when he goes missing with a top-secret document that even a glance at could get an officer court-martialed, Sueño and Bascom take it upon themselves to find him. Meanwhile, Overseas Observer reporter Katie Byrd Worthington is back to make life difficult for top Army brass. When she lands in a Korean jail cell, Sueño and Bascom are sent to get her out-and negotiate against the publication of an incriminating story that could land important military officials in hot water"--